2021
DOI: 10.1038/s41467-021-24919-7
|View full text |Cite
|
Sign up to set email alerts
|

An integrated functional and clinical genomics approach reveals genes driving aggressive metastatic prostate cancer

Abstract: Genomic sequencing of thousands of tumors has revealed many genes associated with specific types of cancer. Similarly, large scale CRISPR functional genomics efforts have mapped genes required for cancer cell proliferation or survival in hundreds of cell lines. Despite this, for specific disease subtypes, such as metastatic prostate cancer, there are likely a number of undiscovered tumor specific driver genes that may represent potential drug targets. To identify such genetic dependencies, we performed genome-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 62 publications
0
12
1
Order By: Relevance
“…Das et al conducted the first genome-scale CRISPRi screen in metastatic PCa models to identify genes required for cell survival [ 62 ]. They demonstrated that Kinesin Family Member 4A (KIF4A) and WD Repeat Domain 62 (WDR62) promote aggressive PCa phenotypes in vitro and in vivo, leading to nominating KIF4A and WDR62 as PCa driver genes, combined with their clinical data.…”
Section: Crispr Screens In Pcamentioning
confidence: 99%
“…Das et al conducted the first genome-scale CRISPRi screen in metastatic PCa models to identify genes required for cell survival [ 62 ]. They demonstrated that Kinesin Family Member 4A (KIF4A) and WD Repeat Domain 62 (WDR62) promote aggressive PCa phenotypes in vitro and in vivo, leading to nominating KIF4A and WDR62 as PCa driver genes, combined with their clinical data.…”
Section: Crispr Screens In Pcamentioning
confidence: 99%
“…We identified a novel circRNA, termed circWDR62, and confirmed that the expression of circWDR62 was significantly upregulated in exosomes derived from TMZ-resistant glioma cells and serum samples from patients with recurrent glioma. Previous evidence indicates that the expression of the host gene WDR62 is significantly upregulated in most tumours and correlates with poor prognosis in multiple cancers [ 39 , 40 ]. Subsequently, an RNase R treatment assay was carried out to confirm the stability of circWDR62.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that PLK1 and KIF4A as biomarkers have a high prognosis value in patients with prostate cancer ( Gao et al, 2018 ; Cao et al, 2020 ; Liu et al, 2020 ; Wu et al, 2020 ; Das et al, 2021 ). PLK1 has been proven to be a potent and promising target for prostate cancer treatment ( Mao et al, 2018 ; Shin et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%